The THE INFLUENCE OF ONLINE CUSTOMER REVIEWS AND ONLINE CUSTOMER RATINGS ON PURCHASE DECISION OF WARDAH PRODUCTS THROUGH THE SHOPEE MARKETPLACE - Erlyasari, Nova; Isnafahrani , Luthfia; Supriono, Supriono (Universitas Indo Global Mandiri Palembang, 2024)
This research aims todetermine the influence of Online Customer Reviews and Online Customer Ratings on Purchase Decisions among consumers of Wardah products through the marketplace. The type of research used in this research is quantitative with an explanatory research approach. This research uses a non-probability sampling approach with purposive sampling technique. The population in this research is consumers of Wardah products who have used and purchased Wardah products through the Shopee marketplace in the past 6 months with 100 respondents. The data used in this research is primary and secondary data. The results of this research show that Online Customer Reviews and Online Customer Ratings have a significant effect on Purchase Decisions. Partially, these 2 independent variables have a significant effect on Purchase Decision.